Leveraging Zakat for Economic Empowerment and Community Development - Ali Mustafa; Abdul Razalli (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This study explores the relationship between zakat as an Islamic financial instrument and the attainment of economic welfare. Zakat functions as a mandatory social mechanism that obliges the wealthy to assist those in need, thereby reducing poverty and promoting equitable income distribution. By channeling wealth from surplus to deficit groups, zakat plays a vital role in fostering social justice and economic stability within the community. In the framework of Islamic economics, welfare encompasses both material and spiritual well-being, achieved through obedience to divine laws as prescribed in the Qur’an, exemplified by the Prophet Muhammad (peace be upon him), and interpreted through scholarly ijtihad. Consequently, welfare in Islam is not merely a static condition but a continuous process that demands collective effort, ethical commitment, and sustained struggle. This paper emphasizes that effective zakat management can serve as a strategic tool for enhancing community welfare and achieving holistic development aligned with Islamic principles.